Towards a plural history of microfinance - James Copestake; Mateo Cabello; Ruth Goodwin-Groen; Robin Gravesteijn; Julie Humberstone (University of Bath, Centre for Development Studies (CDS), 2015)
This paper is concerned with the recent history of microfinance, both for itself and as a case study of the evolution of development ideas and activities. Doing justice to this history, and to all those involved in it will not be easy. Rather than aiming for a full narrative this paper asks what kinds of histories might be told, and with what evidence. The paper contrasts two dominant but oppositional narratives: a mainstream account rooted in neo-classical economics that has applauded the successes of microfinance in expanding financial market opportunities; and a political economy critique that highlights new opportunities for exploitation. We illustrate the differences with particular reference to recent developments in India, before turning to the potential for a more inductive and plural account. A more plural history of microfinance emphasises geographical variation in the expansion of financial services, the influence of prior social relations among users, the organisational culture of suppliers and the political economy of regulation. It is also consistent with the variability and contestability of available empirical evidence about the impact of microfinance over space and time. We illustrate this by drawing on a selection of doctoral research studies, and conclude by cautioning against universal narratives of either successful financial inclusion or adverse incorporation.
Keywords: 330; microfinance; financial inclusion; adverse incorporation; international development; social relations; organisational culture; financial regulation